Predictive Factors of Relapse After Methotrexate Discontinuation in Juvenile Idiopathic Arthritis Patients With Inactive Disease - Azevedo, S (2022)
Objective: To identify predictive factors of relapse after discontinuation of Methotrexate (MTX) in Juvenile Idiopathic Arthritis (JIA) patients with inactive disease. Methods: We conducted a prospective multicenter cohort study of patients diagnosed with JIA using real world data from the Portuguese national register database, Reuma.pt. Patients with JIA who have reached JADAS27 inactive disease and discontinued MTX before the age of 18 were evaluated. Results: A total of 1470 patients with JIA were registered in Reuma.pt. Of the 119 bionaive patients who discontinued MTX due to inactive disease, 32.8% have relapsed. Median time of persistence (using the Kaplan-Meier method and log-rank tests) with inactive disease was significantly higher in patients with more than two years of remission before MTX discontinuation and in those who did not use NSAIDs at time of MTX discontinuation. In Cox regression analyses and after adjustment for age at diagnosis, MTX tapering and JIA category, the use of NSAIDs at the time of MTX discontinuation (HR, 1.98 95%CI 1.03-3.82) and remission time of less than two years before suspension (HR, 3.12 95%CI 1.35-7.13) remained associated with relapse. No association was found between JIA category or the regimen of MTX discontinuation and the risk of relapse. Conclusions: In this large cohort we found that the use of NSAIDs at the time of MTX discontinuation was associated with a two times higher likelihood of relapse. In addition, longer duration of remission before MTX withdrawal reduces the chance of relapse in bionaive JIA patients.